Competition Law - Richard Whish , David Bailey (Oxford university press, 2012)
Whish and Bailey's Competition Law is the definitive textbook on this subject. An authoritative treatment of competition law is paired with an easy-to-follow writing style to make this book a comprehensive guide to the subject; essential reading for law students, practitioners, and officials.